Bone mineral density changes among women initiating blood pressure lowering drugs: a SWAN cohort study. Issue 3 (March 2016) - Solomon, D.; Ruppert, K.; Zhao, Z.; Lian, Y.; Kuo, I.-H.; Greendale, G.; Finkelstein, J.
Abstract Summary We examined the effect of blood pressure lowering drugs on BMD using data from the Study of Women's Health Across the Nation. Thiazide users had a slower decline in BMD compared to nonusers, while decline among ACE inhibitor and beta blocker users were similar to rates in nonusers. Introduction Several blood pressure lowering drugs may affect bone mineral density (BMD), leading to altered fracture risk. We examined the effect of blood pressure lowering drugs on BMD using data from the Study of Women's Health Across the Nation. Methods We conducted a propensity score matched cohort study. Women were initiators of ACE inhibitors (ACEi), beta-blockers (BB), or thiazide diuretics (THZD). Their annualized BMD changes during the 14 years of observation were compared with nonusers. Results Among the 2312 eligible women, we found 69 ACEi, 71 BB, and 74 THZD users who were matched by a propensity score with the same number of nonusers. THZD users had a slower annual percent decline in BMD compared to nonusers at the femoral neck (FN) (−0.28 % vs −0.88 %;p = 0.008) and the spine (−0.74 % vs −1.0 %;p = 0.34), albeit not statistically significant. Annual percent changes in BMD among ACEi and BB users were similar to rates in nonusers. In comparison with BB, THZD use was associated with a trend toward less annualized BMD loss at the spine (−0.35 % vs −0.60 %;p = 0.08) and a similar trend at the FN (−0.39 % vs −0.64 %;p = 0.08); in comparisons with ACEi, THZD was also associated with less loss at the FN (−0.48 % vs −0.82 %;p = 0.02), but not at the spine (−0.40 % vs −0.56 %;p = 0.23). Conclusions Neither ACEi nor BB was associated with improvements in BMD. THZD use was associated with less annualized loss of BMD compared with nonusers, as well as compared with ACEi and BB.